EPCO-06. MOLECULAR DETERMINANTS OF EVOLUTION AND PROGNOSIS AMONG DIFFUSE LOWER GRADE ASTROCYTOMAS. (9th November 2020) - Kumar, Mehul; Cairncross, Gregory; Blough, Michael; Bose, Pinaki
Abstract: Gliomas with wild type (WT) isocitrate dehydrogenase ( IDH ) are considerably more aggressive than those with mutant IDH . To identify putative drivers of the distinct progression trajectories of IDH WT and mutant disease, we analyzed transcriptomes of lower grade astrocytomas (LGAs; grade 2–3) with retention of 1p and 19q from The Cancer Genome Atlas (TCGA; n = 347). Compared to IDH mutant LGAs, we found that PDGF signaling was significantly enriched in IDH WT LGAs and that PDGFA was the top overexpressed gene in this pathway. We identified copy number gains of chromosome 7 in WT LGAs, and methylation of the PDGFA promoter in mutant LGAs, as candidate mechanisms for the differential expression of PDGFA . High PDGFA expression and low PDGFA promoter methylation were significantly associated with poor survival in all LGAs. We also found that PDGFA expression was positively associated with aneuploidy and extracellular matrix-related immunosuppressive features in WT LGAs, underscoring the role of PDGFA as a secreted mitogen. Finally, we show that the proportion of p53 pathway mutations increase significantly with grade in IDH WT gliomas. Taken together, our findings suggest that IDH WT LGAs evolve to higher grades, and ultimately to GBM, by progressive inactivation of the p53 pathway - functioning in concert with a background of increased PDGFA expression. These data emphasize the scope of genomic reprogramming that occurs in gliomas in relation to IDH mutations and further highlight the role of PDGFA in glioma formation, progression, and prognosis. Going forward, this work provides critical biological insight that may inspire new therapeutic strategies to suppress the transformation of IDH WT LGAs to higher-grade cancers.